Denotation and Connotation in Beauty Advertisement: Implication for the teaching of Semantics - Lilik Tri Handayani; Rohmani Nur Indah (LPPM Universitas Bina Sarana Informatika, 2022)
Advertising language sets an important role in conveying the purpose of influencing the consumers. To advertise a beauty product, the choice of words representing the concept of beauty becomes the first concern. This study aims to examine the types of meaning of the words used in a beauty product advertisement. To interpret the lexical meaning in beauty product, the method used in this study is descriptive qualitative analysis on six beauty products, particularly the hand body lotion product by Nivea company. The data were analyzed through Leech theory. The result showed two types of meaning in the body lotion products, namely the denotative and connotative meanings. Denotation occurs more in all of the product compared to the connotative meaning. The implication of the finding contributes to the teaching of semantics to enrich the understanding of the perspective of Leech theory in lexical meaning.